Infotainment technology based on artificial intelligence: Current research trends and future directions - Gamboa Rosales, Nadia Karina; Celaya-Padilla, José María; Galván-Tejada, Carlos E.; Galván-Tejada, Jorge I.; Luna-García, Huitzilopoztli; Gamboa-Rosales, Hamurabi; López Robles, José Ricardo (Iberoamerican Journal of Science Measurement and Communication, 2022)
Objective. To identify the main research, development and innovation themes associated with infotainment systems and artificial intelligence from 2001 to 2022. In addition, to identify the performance and impact of these areas of knowledge using the Scopus database. Design/Methodology/Approach. The research is based on a two-phase analysis. First is an analysis of performance and impact through evaluating the main bibliometric indicators. Secondly, a science mapping of the publications identified within the areas of knowledge with SciMAT. The combination of both phases allows for analyzing the initial and current state of the knowledge areas, identifying the main themes and stakeholders, thereby establishing a framework of reference. Results/Discussion. In general, 44 documents related to infotainment and artificial intelligence systems have been identified in the Scopus database. From 2001 to 2022, 57 research, development, and innovation themes have been identified and ordered, among which the main themes are: HUMAN-COMPUTER-INTERIORATION-(HCI), 5G-MOBILE-COMMUNICATION-SYSTEMS, ACCIDENT-PREVENTION, WIRELESS-AND-MOBILE-COMMUNICATIONS, and VEHICULAR-ADHOC-NETWORKS-(VANETS). A relevant aspect is that two areas are visualized, software and hardware, which are articulated towards the objectives of these technologies, where the user and connectivity are key pillars in its evolution. Conclusions. In terms of performance, the dimension and weight of the literature related to infotainment systems and artificial intelligence has been exposed since its first publication in 2001. Considering the volume of publications and citations recorded growing, it is expected that the development and application of the same will increase in the coming years. Current research shows that infotainment systems and artificial intelligence are growing areas of research with different approaches. In addition, some lines of future research, development, and innovation are needed to deepen these systems, their evolution, and their relationship with other topics from the point of view of hardware or concrete applications. Originality/Value. Both infotainment technologies and artificial intelligence are growing fields, so having a reference framework will be useful to define and develop the most appropriate R&D and innovation lines according to the needs.